E-Gardening Application for Roof Tops Using Android - Dwarakanath, B; Maria Lynda Missier, G; Madhav, S; Navin, P (International Journal of Engineering and Technology, 2018)
The gardening field has a very large amount of need to the society as now a day’s only the greenery is best for a healthy living. This venture depends on the business exchange of things in a general store. The main movement depends on adding the things to the framework alongside the rate which are available in the market and the name of the things which the store will consist of a basic offer. The admin is in charge of all the data up gradation, deletion and editing. The client need to enter his/her details to login and to view and to request for the requirement and send the request [2].